The Graphic Representation of Tōhoku Dialect in Contemporary Japanese Prose - Jaśkiewicz, Hanna (Silva Iaponicarum, 2024)
This paper investigates the language ideologies behind the graphic and graphemic representation of Tōhoku dialect in contemporary Japanese prose. Despite being negatively perceived, recent interest in this variety has prompted its inclusion in literary works. Analyzing ten novels, this research examines authors’ strategies in navigating the complexities of portraying the characteristics of Tōhoku dialect within the frame of the Japanese writing system. Emphasis is placed on the techniques used to represent non-standard phonology of this variety, such as the choice of script as well as other forms of visual representation. Based on the assumption that writers are also carriers of language ideologies (Spitzmüller 2012: 257), the ideological implications of these choices are also established. The findings indicate that while various strategies were employed, there is a tendency to choose hiragana and kanji over katakana, which emphasizes familiarity and the connection with standard Japanese, indicating the influence of the ideology of the national language. Practical factors, such as understandability for potential readers, also play an important role. Some techniques, such as the use of graphic symbols, perpetuate the stereotype about the incomprehensibility of the Tōhoku dialect.